Improving forest land governance: the case of developing a digital archiving system for forest land records in Bangladesh. (1st March 2018) - Barua, S.K.; Abir, U.H.; Boscolo, M.
Land administration in Bangladesh relies significantly on paper-based records which are stored in multiple government offices. This deters public access to land records that breeds inefficiencies. This article assesses the anticipated impacts and challenges of a digital archiving system for the forest land records on the land governance in Bangladesh. The system is expected to contribute to improving land administration and governance in the country by, (i) permanently preserving forest land records, (ii) helping resolve land disputes and fight land grabbing, and (iii) improving the accessibility and transparency of these documents. However, lack of adequate funding and skilled manpower pose challenges to the sustainability and scaling up of undertaken digitization and archiving initiatives. Thus, the capacity for forest land administration should be strengthened. Land-related policy and legislative frameworks should also be reformed to fully realize the advantages of digitization. La ordenación del territorio en Bangladesh se sustenta en gran medida en registros en papel que se almacenan en varias oficinas gubernamentales. Esto impide el acceso público a los registros catastrales, lo que crea ineficiencias. Este artículo evalúa los impactos previstos y los retos de un sistema de archivo digital de los registros de tierras forestales sobre la gobernanza territorial en Bangladesh. Se espera que el sistema contribuya a la mejora de la administración de tierras y a la gobernanza en el país mediante, (i) preservar de forma permanente los registros de tierras forestales, (ii) ayudar a resolver disputas sobre tierras y luchar contra el acaparamiento de tierras, y (iii) la mejora de la accesibilidad y la transparencia de estos documentos. Sin embargo, la falta de financiación adecuada y personal cualificado plantean desafíos a la sostenibilidad y la universalización de las iniciativas emprendidas de digitalización y archivo. Por lo tanto, se debe fortalecer la capacidad de gestión de tierras forestales. Los marcos de políticas y normativos relacionados con la tierra también se deben reformar, para poder disfrutar plenamente de las ventajas de la digitalización.L'administration des terres au Bangladesh s'appuie fortement sur des archives papier, classées dans divers bureaux gouvernementaux. Ceci décourage l'accès public aux enregistrements terriens, résultant en une inefficacité générale. Cet article fait face aux impacts anticipés et au défi que lancerait un système d'archives digitales pour l'enregistrement des terres forestières sur la gestion des terres au Bangladesh. On espère que ce système contribue à l'amélioration de l'administration des terres et de la gestion dans le pays en : (i) préservant les archives des terres forestières de manière permanente, (ii) aidant à résoudre les disputes terriennes et à combattre l'accaparement des terres, et en, (iii) améliorer l'accessibilité et la transparence de ces documents. Une carence de fonds adéquats et de personnel entraîné lance toutefois des défis à la durabilité et à la croissance des initiatives d'archives et de digitalisation. C'est pourtant par ces moyens que la capacité de l'administration forestière pourrait-être fortifiée. Les cadres des politiques associées à la terre, tout comme les cadres législatifs devraient également être réformés pour réaliser pleinement les avantages de la digitalisation.